Fibroblasts stimulate macrophage migration in interconnected extracellular matrices through tunnel formation and fiber alignment. (July 2019) - Ford, Andrew J.; Orbach, Sophia M.; Rajagopalan, Padmavathy
Abstract: In vivo, macrophages and fibroblasts navigate through and remodel the three-dimensional (3D) extra-cellular matrix (ECM). The orientation of fibers, the porosity, and degree of cross-linking can change the interconnectivity of the ECM and affect cell migration. In turn, migrating cells can alter their microenvironment. To study the relationships between ECM interconnectivity and migration of cells, we assembled collagen hydrogels with dense (DCN) or with loosely interconnected networks (LCN). We find that in DCNs, RAW 264.7 macrophages in monocultures were virtually stationary. In DCN co-cultures, Balb/c 3T3 fibroblasts created tunnels that provided conduits for macrophage migration. In LCNs, fibroblasts aligned fibers up to a distance of 100 μm, which provided tracks for macrophages. Intra-cellular and extra-cellular fluorescent fragments of internalized and degraded collagen were detected inside both cell types as well as around their cell peripheries. Macrophages expressed higher levels of urokinase-type plasminogen activator receptor associated protein (uPARAP)/mannose receptor 1 (CD206) compared to α2 β1 indicating that collagen internalization in these cells occurred primarily via integrin-independent mechanisms. Network remodeling indicated by higher Young's modulus was observed in fibroblast monocultures as a result of TGF-β secretion. This work unveils new roles for fibroblasts in forming tunnels in networked ECM to modulate macrophage migration.